2011
DOI: 10.1007/s12011-011-8986-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Elements in Anti-influenza Virus Mushrooms

Abstract: We have determined the trace element composition of anti-influenza virus mushrooms using atomic absorption spectrophotometer. The elements present in greater concentration in Ganoderma lucidum samples are selenium, iron, and zinc, with selenium being the element with the highest concentration of all, at 416 ± 38.5 mg/kg; in Cordyceps militaris samples are iron, selenium, and zinc, with iron being the element with the highest concentration of all, at 291 ± 20.9 mg/kg; in Kuehneromyces mutabilis samples are sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In 2009, Yousfi et al extracted and isolated two other known polyphenols ( 1 and 5 ) and a new compound methyl 5-(3,4-dihydroxyphenyl)-3-hydroxypenta-2,4-dienoate ( 6 ) from the antioxidant components of the fruiting bodies parasitic on Pistacia atlantica , and its structure was determined by NMR and EI-MS [ 13 ]. In the experiment to determine the trace element composition of anti-influenza virus mushrooms, compounds 1 and 5 were once more isolated and extracted from the fruiting bodies of I. hispidus in 2011 [ 14 ]. In 2011 and 2012, Zan et al isolated ten phenolic compounds from methanol extracts of fruiting bodies living on ash, among which inonotusins A ( 7 ) and B ( 8 ) were new natural products.…”
Section: Compounds With Diverse Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Yousfi et al extracted and isolated two other known polyphenols ( 1 and 5 ) and a new compound methyl 5-(3,4-dihydroxyphenyl)-3-hydroxypenta-2,4-dienoate ( 6 ) from the antioxidant components of the fruiting bodies parasitic on Pistacia atlantica , and its structure was determined by NMR and EI-MS [ 13 ]. In the experiment to determine the trace element composition of anti-influenza virus mushrooms, compounds 1 and 5 were once more isolated and extracted from the fruiting bodies of I. hispidus in 2011 [ 14 ]. In 2011 and 2012, Zan et al isolated ten phenolic compounds from methanol extracts of fruiting bodies living on ash, among which inonotusins A ( 7 ) and B ( 8 ) were new natural products.…”
Section: Compounds With Diverse Structuresmentioning
confidence: 99%
“…After feeding mice I. hispidus mushroom containing compounds 1 and 5 , the anti-influenza virus ability of mice was improved, as was the content of trace elements zinc (194 ± 16.9 mg/kg), selenium, and iron in mouse serum. These metal elements are thought to enhance the antiviral ability of the I. hispidus mushroom [ 14 ].…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…The antiviral activity of medicinal fungi may also be related to its trace elements. Wang et al, found that selenium, zinc and magnesium contained in medicinal fungi may play a direct or indirect role in anti-influenza virus [ 112 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Trace elements are essential to immune regulation and infection prevention (Li et al, 2019). The action of C. militaris trace elements and their ability to counteract the influenza virus were analyzed by Wang and Hou (2011) (Wang and Hou, 2011). They orally administered 4 mg/kg/day of C. militaris extracts to treat H1N1-infected mice and monitored mortality and levels of Cu, Zn, Mg, Mn, Se, and Fe in the serum.…”
Section: Trace Elements and Powdersmentioning
confidence: 99%